2019
DOI: 10.1063/1.5066052
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency performance of hydrogenated diamond MOSFETs with alumina

Abstract: Hydrogenated diamond MOSFETs with self-oxidized alumina as a gate dielectric are fabricated. The diamond MOSFETs show a high maximum drain current density of 466 mA/mm at VGS = −6 V, a transconductance of 58 mS/mm, and an off-state breakdown voltage of −53 V. The maximum output power density reaches 745 mW/mm at 2 GHz continuous wave, which is the highest reported value for diamond transistors measured at 2 GHz. The output power value measured is lower than that estimated. Pulse I-V analysis shows that the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…Figure 10 shows the schematic cross-sectional view of HD MOSFET and its large-signal performance. In 2019, diamond MOSFETs with self-oxidized alumina as a gate dielectric with a gate-drain length of 0.8 μm have been demonstrated whose maximum output power density reached 745 mW/mm at 2 GHz, which is presented by Zhou et al 44 Moreover, Yu et al 45 reported a maximum output power density of 182 mW/mm with Al 2 O 3 deposited at a low temperature of 90 C in 2019. In 2020, an HD MISFET with a gate length of 350 nm was fabricated by a self-aligned process, and selfoxidized alumina showed a continuous-wave output power density of 650 mW/mm at 10 GHz.…”
Section: Numerical Modeling Of Hd Fetsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 10 shows the schematic cross-sectional view of HD MOSFET and its large-signal performance. In 2019, diamond MOSFETs with self-oxidized alumina as a gate dielectric with a gate-drain length of 0.8 μm have been demonstrated whose maximum output power density reached 745 mW/mm at 2 GHz, which is presented by Zhou et al 44 Moreover, Yu et al 45 reported a maximum output power density of 182 mW/mm with Al 2 O 3 deposited at a low temperature of 90 C in 2019. In 2020, an HD MISFET with a gate length of 350 nm was fabricated by a self-aligned process, and selfoxidized alumina showed a continuous-wave output power density of 650 mW/mm at 10 GHz.…”
Section: Numerical Modeling Of Hd Fetsmentioning
confidence: 95%
“…62 HD MOSFET with the 2DHG surface channel is greatly influenced by the interface traps in the Al 2 O 3 /C H diamond structure. Pulse IV characterizations have been conducted to analyze the gate-lag and drain-lag effects in diamond transistors, 44,63 and the capacitance-voltage (C-V) measurement was utilized to extract the detailed trap levels and densities. 63,64 The Al 2 O 3 /C H diamond interface exhibits acceptorlike interface traps with much shorter time scales in the microsecond range.…”
Section: F I G U R E 1mentioning
confidence: 99%
“…For example, the Baliga figure of merit, which discloses the block voltage and conduction loss of power devices, varies nonlinearly as a sixth power of the bandgap energy. Along with the high thermal conductivity, large carrier saturation velocity, high carrier mobility, and chemical inertness, diamond is considered a fascinating semiconductor with exceptional physical properties for high‐power, high‐frequency, and harsh environmental (i.e., strong radiation and high‐temperature) electronics applications . The 2‐dimensional hole gas (2DHG) on the hydrogen‐terminated diamond (H‐diamond) surface induced by atmospheric adsorbates or solid‐state acceptor transfer doping has been widely used to develop diamond electronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…В последнее время в литературе все чаще стали появляться работы на тему использования алмазных структур в процессе изготовления полевых транзисторов (field-efect transistors, FETs) [1][2][3][4]. Технологически важной при этом является стадия нанесения тонких диэлектрических слоев на поверхность алмаза, которые обеспечивали бы хорошие изоляционные характеристики.…”
Section: Introductionunclassified
“…Технологически важной при этом является стадия нанесения тонких диэлектрических слоев на поверхность алмаза, которые обеспечивали бы хорошие изоляционные характеристики. В роли таких слоев могут выступать оксид алюминия [1][2][3][4][5], нитрид кремния и оксид циркония [6], оксид молибдена [7] и др. Однако особый интерес в плане применения в качестве диэлектриков представляют собой пленки алмазоподобного углерода (diamond like carbon, DLC), содержащие как алмазные (sp 3 ), так и графитоподобные связи (sp 2 ).…”
Section: Introductionunclassified